2007
DOI: 10.1134/s0026893307050160
|View full text |Cite
|
Sign up to set email alerts
|

Taxon-specific regulation of the SOS response in γ-proteobacteria

Abstract: The SOS response is a cascade of consecutive reactions induced by cell DNA damage. The genes directly involved in these reactions are regulated by LexA, which binds to specific nucleotide sequences in their upstream regions. The presence of such a sequence in the regulatory gene region can be used as a criterion to identify the genes potentially involved in the SOS response. A study was made of the genes whose regulation is specific to particular taxa (Enterobacteriales, Pasteurellales, Vibrionales, Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These findings are interesting since it has been shown that the SOS response system is related to drug resistance in E. coli [ 34 , 35 ] and Staphylococcus aureus [ 35 - 37 ] by mechanisms that are not fully understood. It was reported that the vP2449 gene encoding a toxin exporter responsible for xenobiotic resistance in Vibrionales parahaemolyticus was under the direct control of LexA [ 38 ]. Therefore, it is likely that these drug resistance genes are regulated by LexA, thereby coupling the SOS response to drug resistance in these cyanobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are interesting since it has been shown that the SOS response system is related to drug resistance in E. coli [ 34 , 35 ] and Staphylococcus aureus [ 35 - 37 ] by mechanisms that are not fully understood. It was reported that the vP2449 gene encoding a toxin exporter responsible for xenobiotic resistance in Vibrionales parahaemolyticus was under the direct control of LexA [ 38 ]. Therefore, it is likely that these drug resistance genes are regulated by LexA, thereby coupling the SOS response to drug resistance in these cyanobacteria.…”
Section: Resultsmentioning
confidence: 99%